DISEASE MODIFYING TREATMENTS IN MS: INDUCTION OR ESCALATION?. Issue 11 (14th October 2015) - Williams, Owain H; Harding, Katharine E; Willis, Mark; Pickersgill, Trevor; Wardle, Mark; Robertson, Neil P
Abstract : Background: It is currently unclear whether aggressive induction or stepwise escalation of DMTs provides optimum long term outcomes for patients with MS. Objective: Compare clinical outcomes in clinical practice amongst unmatched patient groups receiving either initial monoclonal induction, injectable DMT only or escalation from injectable DMT. Methods: A subset of a population-based cohort identified 268 patients, with a median follow up post treatment of 5.4 years. Time to disability end points (EDSS) were examined using survival analysis. Results: Monoclonals (25%) pre and post treatment annual relapse rate reduced from 2.28 (±1.92) to 0.28 (±0.42) 88% reduction; injectables (62%) from 1.08 (±0.97) to 0.4 (±1.03), 63% reduction; escalation (13%) had elevated rates of 1.72 (±2.04) to 0.64 (±0.54), only 63% reduction. Time to EDSS4 was shorter for monoclonal against injectable and escalation strategies: 5.7 vs 12 vs 6.8 years, p=0.0002. Time to EDSS6 was similar for the treatment strategies respectively: 14.6 vs 16.4 vs 13.3 years, p=0.13. Conclusions: Patients requiring escalation had relatively worse outcomes, and could be identified as having higher disease activity on treatment initiation. This data suggest that initial selection of DMT class does not significantly affect long term outcome to EDSS6, or conversely, aggressive induction slows the rate of disability progression to EDSS6.